Exome sequencing establishes diagnosis of Alström syndrome in an infant presenting with non‐syndromic dilated cardiomyopathy. (23rd February 2015) - Long, Pamela A.; Evans, Jared M.; Olson, Timothy M.
Abstract : Idiopathic dilated cardiomyopathy is a heritable, genetically heterogeneous disorder characterized by progressive heart failure. Dilated cardiomyopathy typically exhibits autosomal dominant inheritance, yet frequently remains clinically silent until adulthood. We sought to discover the molecular basis of idiopathic, non‐syndromic dilated cardiomyopathy in a one‐month‐old male presenting with severe heart failure. Previous comprehensive testing of blood, urine, and skin biopsy specimen was negative for metabolic, mitochondrial, storage, and infectious etiologies. Ophthalmologic examination was normal. Chromosomal microarray and commercial dilated cardiomyopathy gene panel testing failed to identify a causative mutation. Parental screening echocardiograms revealed no evidence of clinically silent dilated cardiomyopathy. Whole exome sequencing was carried out on the family trio on a research basis, filtering for rare, deleterious, recessive and de novo genetic variants. Pathogenic compound heterozygous truncating mutations were identified in ALMS1, diagnostic of Alström syndrome and prompting disclosure of genetic findings. Alström syndrome is a known cause for dilated cardiomyopathy in children yet delayed and mis‐diagnosis are common owing to its rarity and age‐dependent emergence of multisystem clinical manifestations. At six months of age the patient ultimately developed bilateral nystagmus and hyperopia, features characteristic of the syndrome. Early diagnosis is guiding clinical monitoring of other organ systems and allowing for presymptomatic intervention. Furthermore, recognition of recessive inheritance as the mechanism for sporadic disease has informed family planning. This case highlights a limitation of standard gene testing panels for pediatric dilated cardiomyopathy and exemplifies the potential for whole exome sequencing to solve a diagnostic dilemma and enable personalized care. © 2015 Wiley Periodicals, Inc.